Genome assembly of Stephania longa provides insight into cepharanthine biosynthesis - Shang, Huiying; Lu, Yuan; Xun, Lulu; Wang, Kun; Li, Bin; Liu, Yuxuan; Ma, Tao (Frontiers in Plant Science, 2024)
Stephania longa, renowned for producing cepharanthine, a compound with notable antiviral properties against SARS-CoV-2, holds significant value in the realm of medicinal plants. Due to the gap in genetic knowledge about S. longa, we embarked on creating a high-quality genome assembly to unveil the genetic intricacies and evolutionary narrative of this species.Our phylogenetic analysis not only clarifies the placement of the genus Stephania within the Ranunculales order and also reveals its notably high mutation rate. We delve into the dynamics of gene families, pinpointing expansions and signs of positive selection that likely contribute to the unique metabolic capabilities of Stephania. Our metabolomic profiling across different tissues of S. longa uncovers the complex regulatory mechanisms that orchestrate the biosynthesis and distribution of cepharanthine and related metabolites.Crucially, we identify genes whose expression patterns and evolutionary trajectories suggest pivotal roles in cepharanthine biosynthesis, including those involved in crucial biosynthetic steps. This comprehensive genomic and metabolomic portrait not only enriches our understanding of S. longa's biosynthetic potential but also sets the stage for future investigations into the biosynthesis and therapeutic exploitation of cepharanthine and akin alkaloids.